Electrode Afterload: A Valuable Technique in a Case of Short Electrode Insertion. (14th February 2020) - Riemann, C.; Scholz, S.; Sudhoff, H.; Todt, I.
Abstract : Introduction . The location of the electrode inside the cochlea is important for speech performance. However, many variables, including array length, insertion depth, and individual anatomy, may affect the intracochlear position of the electrode. Insertion deeper than 20 mm and revision surgery are critical situations in which residual hearing and electrode integrity may be at risk. This case report challenges this hypothesis and raises the following question: is it possible to achieve a better speech understanding with an electrode afterload without compromising residual hearing? Case Report . A 73-year-old female patient showed up for evaluation of hearing loss. The patient was operated four times in an external hospital due to cholesteatoma formation in the right ear. Related to a poor aided speech understanding, a CI-surgery was performed. 5 months after the surgery, the subject returned with poor speech understanding. A revision surgery was performed, where the first white marker of the electrode was seen in the round window (20 mm). The electrode was inserted 4 mm deeper into the cochlea. After six and twelve months, the results of the Freiburger monosyllabic speech test improved till 25% and 45%, respectively. Discussion . Hearing preservation is possible with a revisional deeper insertion from 20 mm to 24 mm. In this case, a partial obliteration of an open cavity made the electrode surgically easily accessible. This allowed the deeper insertion during the revision surgery. In a regular surgical field with a posterior tympanotomy, the revision surgery is more challenging and brings the electrode into the risk of an iatrogenic destruction. Conclusion . This case of an electrode afterload after having inserted the electrode initially to mm, demonstrates that hearing can be preserved and speech perception can improve after performing this maneuver.